PENGARUH PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN DAN PERPUTARAN AKTIVA TETAP TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN TAHUN 2017-2021 - Rahmanita Rahmanita; Achmad Hizazi; Rahayu Rahayu (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to examine receivable turnover, inventory turnover, and fixed asset turnover on profitability in food and beverage companies listed on the Indonesia Stock Exchange in 2017-2021. This research is using quantitative method with secondary data. The population used in this research was 85 samples. Sampling is based on a purposive sampling method that follows certain criteria. The analytical method used is multiple linear analysis using SPSS. Based on the results of the partial or t test, receivables turnover variable has no effect on profitability, meanwhile inventory turnover and fixed asset turnover have a significant effect on profitability. Simultaneously accounts receivable turnover, inventory turnover, and fixed asset turnover have a significant effect on profitability in food and beverage companies listed on the Indonesia Stock Exchange. Keywords: Accounts Receivable Turnover, Inventory Turnover, Fixed Asset Turnover, Profitability